A viscoelastic – viscoplastic material model for superalloy applications. (July 2020) - Rouse, J.P.; Engel, B.; Hyde, C.J.; Pattison, S.J.; Whittaker, M.T.; Jones, J.P.; Cockings, B.; Barnard, N.C.
Highlights: Rate dependencies are experimentally observed for a wide range of time scales and load magnitudes. Viscoelastic effects (rate dependency below yield) are often neglected in the literature. A thermodynamically based viscoelastic – viscoplastic model is developed here using RR1000 data. Model parameter determination methods are proposed and demonstrated for 750 °C isothermal conditions. Extensions to include an-isothermal effects are proposed using the thermodynamic basis. Abstract: An understanding of rate dependency over a wide range of time scales is vitally important in approximating the transient response of critical components operating in extreme environments. Many examples of viscoplastic model formulations can be found in the literature, wherein all rate dependency is assumed to occur after yielding. Such models neglect any viscous effects during elastic deformation. In the present work, a unified viscoelastic – viscoplastic material model is developed for the Nickel superalloy RR1000. Particular emphasis is placed on model parameter determination, which is accomplished using standard cyclic plasticity and stress relaxation experimental data.